Pengembangan Aplikasi Si Calang (Situs Candi di Malang) Berbasis Virtual Reality Sebagai Media Pembelajaran IPS - Ningsih, Mia; Kurniawan, Bayu (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2024)
In this digital era, the introduction of historical sites such as temples has begun to interact with technology, one of which is based on virtual reality. Therefore, the aim of this study is to develop Si Calang (Situs Candi di Malang) application which is based on virtual reality as a learning media for VII grade social science class at the level of SMP/MTs. This study used the RD research method with the ADDIE development model. The results of this research and development show that the percentage of the total score from the material validator one is 94.2% and from the material validator two is 90.3%, and from the media validators one and two get the same total percentage score, which is 95.4%. While the results of the trials on prospective users of VII grade students obtained an average percentage score of 85.3%. Based on these results, Si Calang learning media is very suitable to be used as social science learning media for VII grade of social science class at the level of SMP/MTs. The follow-up recommendation from this research and development is by conducting experimental research activities in class which aim to test the effectiveness of using the product on students..